1973
DOI: 10.1037/h0034829
|View full text |Cite
|
Sign up to set email alerts
|

Organizational, work, and personal factors in employee turnover and absenteeism.

Abstract: Research carried out over the past 10-12 years concerning factors related to turnover and absenteeism in work situations is critically examined. On a general level, overall job satisfaction was found to be consistently and inversely related to turnover. More specifically, in an effort to break down the global concept of job satisfaction, various factors in the work situation were analyzed as they related to withdrawal behavior. Four categories of factors, each representing one "level" in the organization, were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

48
1,121
7
40

Year Published

1996
1996
2014
2014

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 1,685 publications
(1,216 citation statements)
references
References 53 publications
48
1,121
7
40
Order By: Relevance
“…Previous research has shown the importance of expectations as referents in determining satisfaction with a job (Porter & Steers, 1973) and with various products (Bolton & Drew, 1991;Anderson & Sullivan, 1993). The results of our first study broaden these findings to include the realm of numerical outcomes such as test scores or bowling scores.…”
Section: Chapter 7; General Discussion and Conclusionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous research has shown the importance of expectations as referents in determining satisfaction with a job (Porter & Steers, 1973) and with various products (Bolton & Drew, 1991;Anderson & Sullivan, 1993). The results of our first study broaden these findings to include the realm of numerical outcomes such as test scores or bowling scores.…”
Section: Chapter 7; General Discussion and Conclusionmentioning
confidence: 99%
“…For example, the concepts of met and unmet expectations have been used in research on employees' socialization into organizations. Porter and Steers (1973) things as pay and benefits as well as organizational roles and responsibility. According to these authors, unmet expectations lead to dissatisfaction, especially when there is disconfirmation of important expectations.…”
mentioning
confidence: 99%
“…Absenteeism and turnover are sometimes described as means of withdrawing as a response to job dissatisfaction, exhaustion, burnout, and depression (Maslach, Schaufeli, and Leiter, 2001;Spector et al, 2006). A wide variety of factors can affect absenteeism and turnover, including health, psychological disorders, stress, social norms, culture, conflict with management, and individual differences (for examples of research on several of these topics, see Aldana and Pronk, 2001;Porter and Steers, 1973;and Podsakoff, LePine, and LePine, 2007). For example, family conflict (such as spousal abuse) and unhealthy activities (such as substance abuse) have also been shown to result in higher rates of absence and turnover (Mighty, 1997;McFarlin and Fals-Stewart, 2002).…”
Section: Workplace Consequencesmentioning
confidence: 99%
“…In a qualitative review of early turnover research, Porter and Steers (1973) concluded that, at that time, much of the turnover process literature focused primarily on the relationship between job satisfaction and voluntary turnover. A few years later, Mobley (1977) proposed that low levels of satisfaction with one's job leads to thoughts of leaving the organization, which lead to searching for alternative jobs and evaluating alternatives, which leads to turnover intentions, and which ultimately results in an employee deciding to quit the organization.…”
Section: Withdrawal Behavior and Turnover Intentionsmentioning
confidence: 99%
“…In a qualitative review of early turnover research, Porter and Steers (1973) proposed that low levels of satisfaction with one's job leads to thoughts of leaving the organization, which lead to searching for alternative jobs and evaluating alternatives, which leads to turnover intentions, and which ultimately results in an employee deciding to quit the organization. Thus, Mobley positioned turnover intentions as the most proximal antecedent to turnover, and job satisfaction as a more distal antecedent.…”
Section: Withdrawal Behavior and Turnover Intentionsmentioning
confidence: 99%